Dimensional Accuracy of Stone Casts Made from Silicone-Based Impression Materials and Three Impression Techniques - Vitti,Rafael Pino (2013)
The aim of this study was to measure and compare the dimensional accuracy of stone casts of a partially edentulous mandibular arch made by two condensation silicones, two addition silicones and three impression techniques (1-step putty/light-body, 2-step putty/light-body and monophase technique). A partially edentulous standard stainless steel mandibular arch cast was obtained with reference points on the permanent mandibular right and left canines, and permanent mandibular right and left second molars. The anteroposterior distances (between the mandibular left canine and second molar and between the mandibular right canine and second molar) and transverse distances (between the mandibular left and right canines and between the mandibular left and right second molars) of stainless steel cast were measured by a microscope at 30× magnification and 0.5 µm accuracy. All impressions were made with condensation or addition silicones. The 1- and 2-step putty/light-body impressions were accomplished with putty and light-body materials and the monophase impressions with light-body material only. After the impression procedures, accuracy of each material and technique was assessed measuring the stone casts poured (n=5) from the impressions, by the same microscope. The differences between the values of stone cast and stainless steel cast were calculated, presented as percentages and analyzed statistically by two-way ANOVA and the means compared by Tukey's test (α=0.05). All distances measured on stone casts showed altered dimensions with significantly negative linear changes (shrinkage) as compared to those of the stainless steel cast. The stone casts made from the addition silicones were dimensionally more accurate. No differences were found among the impression techniques.